Disadvantaged students' academic performance: analysing the zone of proximal development - De Villiers, Abraham Benjamin (Department of Psychology, 2023)
The aim of the study is to investigate the practical application of Vygotsky's construct of the Zone of Proximal Development to the selection of disadvantaged students in higher education. There is a need in post-apartheid South Africa, with its legacy of inequality in educational experiences, to find accurate and fair predictors of academic performance that would act as alternatives to matriculation marks and static tests. The study relates the students' response to mediation to their academic performance and analyses the role that non-cognitive factors such as motivation, approaches to learning and learning strategies play in cognitive performance. The investigation was done in the form of different studies using over 400 first year students at the Peninsula Technikon as subjects. The first study focused on the effectiveness of the mediated lessons that form part of the two dynamic tests using a Solomon Four Group and a Two Group design. The second study made a comparison between the predictive validity of past academic achievement conventional static tests, several non-cognitive variables as well as the two dynamic tests. In the third study the students' response to a period of mediation was analysed. The fourth study focused on comparing different groups of students according to the following classification: schooling, gender, language, type of course and assessment and level of course to see whether any of the variables would have a moderator effect Finally a differention was made between the profiles of more successful as opposed to less successful students. The weight of evidence of the study indicates that it is possible to find alternatives to matriculation marks and static tests in selecting disadvantaged students by making use of the concept of the Zone of Proximal Development The results further showed that disadvantaged students are not a homogeneous group. Although the matriculation marks seemed to be the best single predictor of academic performance for the total group of students, alternative predictors were identified when looking at different subgroups. Modifiability (students' response to mediation) had a moderator effect on the predictive power of various variables. For the less modifiable group of students, the matriculation marks and, to a certain extent, static tests were good predictors, while for the more modifiable group of students a dynamic test proved to be a significant predictor of academic performance. The implications of the findings for the selection and academic development of disadvantaged students are discussed.